The Rationality of Political Parties in Selecting Regional Head Candidates (Dodi Reza Alex Noerdin – Beni Hernedi) in Musi Banyuasin Regency in 2017 - Putra, Aji Wahyu (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2023)
This study examines what is related to the rationality of political parties in determining regional head candidates (Dodi Reza Alexnoerdin – Beni Hernedi) Musi Banyuasin Regency in 2017. This paper describes how each political party rationality consisting of PDIP, Golkar, PKB, PKS, Democrats in selecting and determining candidates for Regional Heads based on arguments and reasons that are indeed seen from the quality of the Muba Regional Head candidates (Dodi Reza Alexnoerdin and Beni Hernedi), political experience, proposed programs and his popularity so that it becomes a benchmark for becoming Head Muba Region in 2017. The method used in this study is a qualitative method by analyzing, understanding and researching a phenomenon that occurs with the aim of describing the problem of the object of research. Data collection in the study was carried out through interviews and documentation. The results show that the factors behind the rationality of political parties determine the candidates for regional head (Dodi Reza Alexnoerdin and Beni Hernedi) in Muba Regency in 2017 because of the rationality that exists from the PDIP, Golkar, PKB, PKS, and Democrat parties saying there is a high potential for This pair of candidates, both in terms of electability, political experience, popularity, and programs that were socialized by candidates Dodi Reza and Beni Hernedi are considered very good and can improve the performance of the Muba area, as well as the reasons from several parties that have been mentioned earlier that from the figure of a pair This candidate has met the requirements and is eligible to run for regional head and deputy regional head in accordance with the experiences of the candidate pairs Dodi and Beni and the quality he has is very good to advance in the 2017 Muba Pilkada.